Carbon black master batch, polypropylene compound and preparation method and application thereof
By using high-pigment carbon black with specific particle size and oil absorption value in a polypropylene compound, combined with mesoporous substances, polar talc, auxiliary antioxidants and maleic anhydride grafts, a carbon with excellent dispersion ability is prepared Black masterbatch solves the problem of color streaks caused by carbon black color mixing in polypropylene melt and achieves a high-quality appearance of polypropylene composites.
Patent Information
- Application Number
- CN202411489407.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-24
AI Technical Summary
In the automotive field, especially in the context of the rapid development of new energy vehicles, when the carbon black added to the polypropylene melt is colored, the carbon black content is ≤4‰, and the existing technology is difficult to effectively solve this problem. .
Using high-pigment carbon black with specific particle size and oil absorption value, combined with mesoporous substances, polar talc, auxiliary antioxidants and maleic anhydride grafts, a carbon black masterbatch with excellent dispersion ability is prepared. Carbon black reduces the distribution gradient of carbon black in the resin matrix and avoids the occurrence of color streaks.
Effectively avoid the color stripes caused by uneven carbon black dispersing in polypropylene melts, improve the appearance quality of polypropylene complexes, and apply to high requirements for internal and external decoration components in the car.
Smart Images

Figure CN119331376A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of modified plastics, and more specifically, relates to a carbon black masterbatch, a polypropylene compound, and a preparation method and use thereof. Background Art
[0002] Polypropylene has the advantages of low density, low price and easy processing, and has been widely used in the automotive industry. In recent years, with the intensification of competition in the automotive industry, especially the rapid development of new energy vehicles, the structure and color design of automotive interior and exterior parts have undergone unprecedented changes, such as integrated design, gradient wall thickness, novel leather grain, and bright colors have begun to be used in automotive interior and exterior decoration. These new designs and new colors have brought consumers a refreshing experience, but they are often prone to various appearance defects, one of which is color streaks, which are difficult to solve with existing methods. These have posed new challenges to the formulation design and molding processing performance of traditional automotive materials.
[0003] There are many reasons for the generation of color stripes, such as color stripes on the weld line caused by the hedging of polypropylene melt, color stripes caused by the turbulent flow of polypropylene melt, and color stripes caused by the convergence of polypropylene due to multiple gates, wall thickness changes, holes, etc. in the mold. For the first type, there are related patents for research, such as patent CN107459705A, which studies the color difference of the weld line of high-gloss polypropylene. By adding random copolymer polypropylene with higher fluidity than the base polypropylene, the distribution width of the molecular weight of polypropylene is broadened, and the interlacing and entanglement of the molecular chains during the front-end welding of the material flow are promoted, so as to obtain a better welding effect; in addition, the high-flow polybutene-1 has good compatibility and melt dispersibility with polypropylene, and has a lower melting point. Its linear molecules are conducive to the interlacing in the base resin, which is conducive to the lubrication and dispersion of inorganic particles during the welding process, and effectively avoids the accumulation of inorganic particles to form discoloration stripes or scratches.
[0004] As for flow disturbance, existing patents mainly focus on flow marks, such as patent CN112679842A, which mainly focuses on tiger stripes in flow marks. By adding a small amount of homopolymer polypropylene with a specific high molecular weight to the polypropylene composition system to improve the melt elasticity, the problem of flow marks on the surface of the material is fundamentally solved. As for color stripes caused by flow disturbance, there is no patent research yet.
[0005] At present, it is found in a large number of applications that the main reason for the color streaks is the uneven dispersion of the toner in the polypropylene melt. This unevenness can be solved by adding toner dispersants, strengthening the dispersing capacity of processing equipment, selecting specially treated toners, improving the melt flow path, etc. However, in the current application of new automotive designs and new colors, there is a special situation. Regardless of the color, such as brown, blue, green, beige, gray, etc., carbon black must be added to the toner formula for color adjustment, and when the carbon black content is ≤4‰, the above-mentioned color streaks are very likely to occur. How to improve the color streaks caused by this carbon black color adjustment has become a technical problem that needs to be solved urgently. Summary of the invention
[0006] In view of the above-mentioned existing technical problems, the primary purpose of the present invention is to provide a carbon black masterbatch.
[0007] The second object of the present invention is to provide a method for preparing carbon black masterbatch.
[0008] The third object of the present invention is to provide a use of a carbon black masterbatch in preparing a polypropylene compound or in the automotive field.
[0009] A fourth object of the present invention is to provide a polypropylene composite.
[0010] A fifth object of the present invention is to provide a method for preparing a polypropylene composite.
[0011] A sixth object of the present invention is to provide a use of a polypropylene compound in the automotive field.
[0012] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0013] A carbon black masterbatch, comprising the following components by weight: 10-20 parts of carbon black, 10-20 parts of mesoporous material, 10-20 parts of polar talc, 40-70 parts of maleic anhydride grafted material, and 0.2-1 part of auxiliary antioxidant; the D50 particle size of the carbon black is ≤20nm, and the oil absorption value of the carbon black is ≤100cm 3 / 100g.
[0014] Through research, the inventors found that the main reason for the current color streaks is due to different polarity. The distribution of trace carbon black at the front end of the polypropylene melt flow and inside the melt is different. When the polypropylene melt converges, becomes disordered, and impacts, color streaks are generated.
[0015] Therefore, in the present invention, high-pigment carbon black with an oil absorption value and a particle size within a specific range is used to replace conventional carbon black. This high-pigment carbon black has the characteristics of small particle size and easy dispersion, which increases the dispersion ability of carbon black and reduces the distribution gradient problem of carbon black in the resin matrix, thereby better avoiding the generation of color streaks.
[0016] Furthermore, the present invention also adds maleic anhydride grafts to the carbon black masterbatch, which are more easily distributed at the front end and surface of the resin matrix melt. At the same time, based on the interaction between polarity and non-polarity, polar talcum powder can be carried to the front end and surface of the resin matrix melt, diluting the carbon black content there, thereby better avoiding the generation of color stripes. The polarity of talcum powder can solve the polarity distribution problem inside the polypropylene melt and reduce the aggregation of carbon black at the front end and surface of the melt.
[0017] Furthermore, the present invention uses a mesoporous substance mixed with carbon black, and it is speculated that the mesoporous substance can adsorb carbon black, so that the carbon black is more evenly distributed in the resin matrix melt; in addition, the adsorption of the mesoporous substance can also destroy the agglomeration of carbon black particles. By adsorbing and destroying the agglomeration of carbon black particles, the carbon black is evenly dispersed in the resin matrix melt, thereby avoiding the generation of color stripes. In addition, the present invention also adds a secondary antioxidant to the carbon black masterbatch, and the secondary antioxidant can reduce the degradation of the carbon black masterbatch.
[0018] The present invention provides a carbon black masterbatch. By adopting carbon black with a specific particle size and oil absorption value, and matching mesoporous material, polar talcum powder, auxiliary antioxidant and maleic anhydride grafted material, the prepared carbon black masterbatch has excellent dispersibility, is more evenly distributed at the flow front end of a resin matrix melt and inside the melt, and when the polypropylene melt converges, is disordered and hedged, the generation of color stripes is better avoided.
[0019] Preferably, the D50 particle size of the carbon black is 7 to 20 nm. More specifically, the D50 particle size of the carbon black is 13 to 19 nm. Specifically, the D50 particle size of the carbon black in the present invention can be 7 nm, 9 nm, 13 nm, 15 nm, 16 nm, 19 nm, etc., or an interval range formed by any of the above values, such as 7 to 13 nm, 15 to 20 nm, etc., and the present invention is not limited thereto. More specifically, the test method for the D50 particle size of the carbon black is: GB / T3780.17-2017.
[0020] Preferably, the oil absorption value of the carbon black is 40 to 100 cm 3 More specifically, the carbon black has an oil absorption value of 46 to 98 cm 3 Specifically, the oil absorption value of the carbon black in the present invention can be 41cm 3 / 100g、46cm 3 / 100g、57cm3 / 100g、61cm 3 / 100g、69cm 3 / 100g、98cm 3 / 100g, etc., or the interval formed by any of the above values, such as 40-50cm 3 / 100g, 66~72cm 3 / 100g, etc., the present invention is not limited thereto. More specifically, the test method for the carbon black oil absorption value is: GB / T 3780.2-2017.
[0021] Preferably, the pore size of the mesoporous material is 2 to 13 nm; and / or
[0022] The mesoporous material is selected from one or more of zeolite, diatomaceous earth, molecular sieve and mesoporous carbon.
[0023] Preferably, the pore size of the mesoporous material is 6 to 12 nm. More specifically, the pore size of the mesoporous material is 8 to 10 nm. Within this preferred range, the number of color stripes and the visibility of color stripes can be better reduced. The pore size test method of the mesoporous material is: using nitrogen as an adsorbent, using TriStarⅡplus 3030, and testing the pore size of the mesoporous material in accordance with the national standard GB / T 21650.2-2008.
[0024] Preferably, the polar talc is organic carboxylic acid coated modified talc; and / or
[0025] The D50 particle size of the polar talc is ≤18 μm.
[0026] Preferably, the D50 particle size of the polar talc is 1 to 11 μm. Further preferably, the D50 particle size of the polar talc is 1.5 to 4 μm. Specifically, the D50 particle size of the polar talc in the present invention can be 2.7 μm, 5 μm, 11 μm, etc., or an interval range formed by any of the above values, such as 2 to 4 μm, 5 to 7 μm, etc., and the present invention is not limited thereto. More specifically, the test method for the D50 particle size of the polar talc is: GB / T 15344-2012.
[0027] Preferably, in the organic carboxylic acid coated modified talc, the content of the organic carboxylic acid is 0.4-1.2 wt %. Further preferably, the content of the organic carboxylic acid is 0.8-1.0 wt %. Within this preferred range, the number of color stripes and the visibility of color stripes can be better reduced.
[0028] Preferably, the organic carboxylic acid is selected from maleic acid-acrylic acid copolymers.
[0029] Preferably, the preparation method of the organic carboxylic acid coated modified talc is as follows: talc is mixed with a solvent, and then maleic acid-acrylic acid copolymer is added and mixed evenly, and dried to obtain the organic carboxylic acid coated modified talc.
[0030] Preferably, the maleic anhydride grafted product is selected from one or more of maleic anhydride grafted polypropylene and maleic anhydride grafted POE; and / or
[0031] The melt flow rate of the maleic anhydride grafted product at 230° C. and 2.16 kg is 3 to 120 g / 10 min; and / or
[0032] The grafting rate of the maleic anhydride grafted product is 0.5 to 1.5%.
[0033] Specifically, the maleic anhydride grafted polypropylene may be maleic anhydride grafted homopolypropylene and / or maleic anhydride grafted copolymer polypropylene.
[0034] Specifically, the test method for the melt flow rate of maleic anhydride grafts is: GB / T 3682-2018. The test method for the grafting rate of maleic anhydride grafts is: acid-base neutralization titration method.
[0035] Preferably, the auxiliary antioxidant is a phosphite antioxidant. More specifically, the phosphite antioxidant includes but is not limited to tris[2,4-di-tert-butylphenyl]phosphite, bis(2,4-di-tert-butylphenol)pentaerythritol diphosphite, 3,9-bis(2,4-dicumylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, and the like.
[0036] Furthermore, the present invention seeks to protect a method for preparing a carbon black masterbatch, comprising the following steps: mixing carbon black and a mesoporous material, then adding polar talcum powder, maleic anhydride grafted material and a secondary antioxidant, mixing evenly, and granulating to obtain a carbon black masterbatch.
[0037] Furthermore, the present invention claims protection for a polypropylene composite, comprising the following components, by weight: 28 to 100 parts of polypropylene resin, 0.1 to 2 parts of the carbon black masterbatch, 0 to 1 part of an antioxidant, 0 to 0.5 parts of a light stabilizer, 0 to 0.5 parts of a lubricant, 0 to 10 parts of a polyethylene resin, 0 to 30 parts of an elastomer, and 0 to 30 parts of a mineral powder.
[0038] Furthermore, the present invention seeks to protect a polypropylene composite, comprising the following components, by weight: 28 to 100 parts of polypropylene resin, 0.1 to 2 parts of the carbon black masterbatch, 0.2 to 1 part of an antioxidant, 0.1 to 0.5 parts of a light stabilizer, 0.1 to 0.5 parts of a lubricant, 0 to 10 parts of a polyethylene resin, 0 to 30 parts of an elastomer, and 0 to 30 parts of a mineral powder.
[0039] Furthermore, the present invention seeks to protect a polypropylene composite, comprising the following components, by weight: 28 to 100 parts of polypropylene resin, 0.1 to 2 parts of the carbon black masterbatch, 0.2 to 1 part of an antioxidant, 0.1 to 0.5 parts of a light stabilizer, 0.1 to 0.5 parts of a lubricant, 2 to 10 parts of a polyethylene resin, 10 to 30 parts of an elastomer, and 20 to 30 parts of a mineral powder.
[0040] Specifically, the amount of the antioxidant in the present invention is 0.4 parts, 0.6 parts, 0.8 parts, etc., or an interval range formed by any of the above values; specifically, the amount of the light stabilizer in the present invention is 0.2 parts, 0.3 parts, 0.4 parts, etc., or an interval range formed by any of the above values; specifically, the amount of the lubricant in the present invention is 0.2 parts, 0.3 parts, 0.4 parts, etc., or an interval range formed by any of the above values; specifically, the amount of the polyethylene resin in the present invention is 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, or an interval range formed by any of the above values; specifically, the amount of the elastomer in the present invention is 15 parts, 18 parts, 20 parts, 23 parts, 25 parts, 27 parts, etc., or an interval range formed by any of the above values; specifically, the amount of the mineral powder is 22 parts, 24 parts, 26 parts, 28 parts, etc., or an interval range formed by any of the above values.
[0041] Preferably, the mass percentage of the polypropylene resin in the polypropylene composite is not less than 28%. Further preferably, the mass percentage of the polypropylene resin in the polypropylene composite is not less than 70%.
[0042] Preferably, the polypropylene resin is one or more of copolymer polypropylene and homopolypropylene. Further preferably, the polypropylene resin is homopolypropylene. Under this preference, the prepared polypropylene composite has fewer color stripes and lower color stripe visibility.
[0043] Preferably, the melt flow rate of the polypropylene resin at 230°C and 2.16Kg is 2 to 100g / 10min. Specifically, the melt flow rate of the polypropylene resin at 230°C and 2.16Kg is 2.6 to 90g / 10min. Specifically, the melt flow rate of the polypropylene resin in the present invention can be 10g / 10min, 30g / 10min, 60g / 10min, 90g / 10min, etc., or an interval range formed by any of the above values, such as 5 to 25g / 10min, 45 to 75g / 10min, etc., and the present invention is not limited thereto. Specifically, the test method for the melt flow rate of the polypropylene resin is: GB / T 3682-2018.
[0044] Preferably, the polyethylene resin is one or more of high-density polyethylene (HDPE) and low-density polyethylene (LDPE).
[0045] Preferably, the melt flow rate of the polyethylene resin at 190° C. and 2.16 kg is 2 to 17 g / 10 min. Specifically, the test method for the melt flow rate of the polyethylene resin is: GB / T3682-2018.
[0046] Preferably, the elastomer is a polyolefin elastomer (POE). The melt flow rate of the elastomer at 190°C and 2.16 kg is 0.3 to 17 g / 10 min. The test method for the melt flow rate of the elastomer is: GB / T 3682-2018.
[0047] Preferably, the mineral powder may be one or more of talc, whisker, and mica. The D50 particle size of the mineral powder is ≤18 μm. Preferably, the D50 particle size of the mineral powder is 1 to 11 μm. Preferably, the D50 particle size of the mineral powder is 1.5 to 4 μm.
[0048] Preferably, the lubricant is selected from one or more of amide lubricants, stearic acid lubricants, and fatty acid lubricants.
[0049] Preferably, the primary antioxidant is a hindered phenol antioxidant. Specifically, the hindered phenol antioxidant includes but is not limited to pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, etc.
[0050] The light stabilizer includes but is not limited to nickel dibutyl dithiocarbamate, bis-2,2,6,6-tetramethylpiperidinol sebacate (light stabilizer 770), poly{[6-[(1,1,3,3-tetramethylbutyl)amino]]-1,3,5-triazine-2,4-[(2,2,6,6,-tetramethyl-piperidinyl)imino]-1,6-hexanediol[(2,2,6,6-tetramethyl-4-piperidinyl)imino]}, etc. Preferably, the light stabilizer is a hindered amine light stabilizer.
[0051] Furthermore, the present invention claims protection for a method for preparing a polypropylene composite, wherein polypropylene resin, carbon black masterbatch and other substances contained in the polypropylene composite are mixed, melt-extruded and granulated to obtain the polypropylene composite.
[0052] Preferably, a twin-screw extruder is used for extrusion, and the aspect ratio of the twin-screw extruder is 36 to 48:1.
[0053] Preferably, the temperature of melt extrusion is 180-230° C., and the vacuum degree of melt extrusion is ≤-0.1 MPa.
[0054] Preferably, the screw speed of the twin-screw extruder is 300-700 rpm.
[0055] Furthermore, the present invention claims a use of a polypropylene compound in the automotive field. Specifically, the polypropylene compound is suitable for preparing door panels, pillars, bumpers, etc., especially in occasions with high requirements on appearance.
[0056] Compared with the prior art, the present invention has the following beneficial effects:
[0057] The present invention provides a carbon black masterbatch. By adopting carbon black with a specific particle size and oil absorption value, and matching mesoporous material, polar talcum powder, auxiliary antioxidant and maleic anhydride grafted material, the prepared carbon black masterbatch has excellent dispersibility, is more evenly distributed at the flow front end of a resin matrix melt and inside the melt, and when the polypropylene melt converges, is disordered and hedged, the generation of color stripes is better avoided. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 This is a partial appearance diagram of the polypropylene composite prepared in Comparative Example 4. DETAILED DESCRIPTION
[0059] The present invention is further described below in conjunction with the specification and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0060] The raw materials of the embodiments and comparative examples are as follows:
[0061] Polypropylene resin 1: homopolymer polypropylene resin, PP T30S, melt flow rate of 2.6 g / 10 min at 230°C and 2.16 kg, Lanzhou Petrochemical.
[0062] Polypropylene resin 2: homopolymer polypropylene resin, PP Y26, melt flow rate of 26 g / 10 min at 230°C and 2.16 kg, from Zhenhai Refining and Chemical.
[0063] Polypropylene resin 3: copolymer polypropylene resin, PP BX3900, melt flow rate of 60 g / 10 min at 230° C. and 2.16 kg, manufactured by SK of Korea.
[0064] Polypropylene resin 4: copolymerized polypropylene resin, PP BX3920, melt flow rate of 90 g / 10 min at 230° C. and 2.16 kg, manufactured by SK of Korea.
[0065] Maleic anhydride grafted polypropylene: LEP-1B, maleic anhydride grafting rate is 1.0%, Shenyang Ketong.
[0066] Carbon black 1: P45, D50 particle size is 13nm, oil absorption value is 46cm 3 / 100g, Tianjin Golden Land.
[0067] Carbon black 2: C111, D50 particle size is 15nm, oil absorption value is 98cm 3 / 100g, Tianjin Golden Land.
[0068] Carbon black 3: SM100, D50 particle size is 19nm, oil absorption value is 69cm 3 / 100g, Tianjin Golden Land.
[0069] Carbon black 4: S666, D50 particle size is 28nm, oil absorption value is 70cm 3 / 100g, Tianjin Golden Land.
[0070] Carbon black 5: C126, D50 particle size is 16nm, oil absorption value is 115cm 3 / 100g, Tianjin Golden Land.
[0071] Primary antioxidant: 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, antioxidant 1790, commercially available.
[0072] Secondary antioxidant: tris[2,4-di-tert-butylphenyl]phosphite, antioxidant 168, commercially available.
[0073] Light stabilizer: poly{[6-[(1,1,3,3-tetramethylbutyl)amino]]-1,3,5-triazine-2,4-[(2,2,6,6,-tetramethyl-piperidinyl)imino]-1,6-hexanediyl[(2,2,6,6-tetramethyl-4-piperidinyl)imino]}, commercially available.
[0074] Lubricant: Zinc stearate, commercially available.
[0075] Mineral powder: talc, HTP2L, D50 particle size 2.4μm, imi ratio.
[0076] Polar talcum powder 1, talcum powder HTP2L is mixed with water, and then maleic acid-acrylic acid copolymer (source: Wengjiang reagent) is added and mixed evenly, and dried to obtain organic carboxylic acid-coated modified talcum powder (the content of organic carboxylic acid is 1wt%).
[0077] Polar talcum powder 2, talcum powder HTP2L is mixed with water, and then maleic acid-acrylic acid copolymer (Wengjiang reagent) is added and mixed evenly, and dried to obtain organic carboxylic acid-coated modified talcum powder (the content of organic carboxylic acid is 0.4wt%).
[0078] Mesoporous material 1: SBA-15 molecular sieve, pore size 10 nm, Oss catalysis.
[0079] Mesoporous material 2: MCM-41 molecular sieve, pore size 2 nm, Oss catalysis.
[0080] Mesoporous material 3: Mesoporous carbon, pore diameter 6nm, Beike New Materials.
[0081] Elastomer: POE 8150, with a melt flow rate (MFR) of 0.5 g / 10 min at 190° C. and 2.16 kg, from Dow Chemical.
[0082] Unless otherwise specified, the components (such as antioxidants, lubricants) selected in the parallel examples and comparative examples are all the same commercially available products.
[0083] Example 1
[0084] The weight parts of the raw materials used in Example 1 are shown in Table 1.
[0085] A carbon black masterbatch, comprising the following specific steps:
[0086] The carbon black and the mesoporous material are mixed and ground, and then polar talcum powder, maleic anhydride grafted polypropylene and auxiliary antioxidant are added into an internal mixer, mixed evenly, and granulated to obtain carbon black masterbatch.
[0087] A polypropylene composite, comprising the following steps:
[0088] Add polypropylene, polyethylene, elastomer and talcum powder into a mixer and mix evenly, then add the above-mentioned carbon black masterbatch and continue to mix evenly, add it to the main feeding port of the twin-screw extruder, carry out melt blending, and vacuum extrusion granulation (temperature is 200°C, vacuum degree is -0.1MPa, screw speed is 600rpm, aspect ratio is 44:1) to obtain a polypropylene composite.
[0089] Embodiment 2 to Embodiment 16
[0090] The weight parts of the raw materials used in the following examples are shown in Table 1.
[0091] The specific preparation steps of the following examples are the same as those of Example 1.
[0092] Comparative Example 1 to Comparative Example 6
[0093] The weight parts of the raw materials used in the following comparative examples are shown in Table 2.
[0094] The specific preparation steps of other comparative examples are the same as those of Example 1.
[0095] Table 1
[0096]
[0097]
[0098] Table 2 shows the formula components of each comparative example:
[0099] Table 2
[0100]
[0101] The polypropylene composites prepared in the above examples and comparative examples were injection molded to prepare test specimens. The size of the test specimens was 350*100 mm. The appearance was evaluated. The evaluation criteria are shown in Table 3.
[0102] Table 3
[0103]
[0104]
[0105] Table 4 shows the performance test results of various embodiments and comparative examples.
[0106] Table 4
[0107]
[0108] As can be seen from the data of the examples, the present invention provides a carbon black masterbatch, which has excellent dispersibility and is more evenly distributed at the flow front end of the resin matrix melt and inside the melt, and when the polypropylene melt merges, turbulently, and counteracts, the generation of color stripes is better avoided. The number of color stripes of the polypropylene compound added with the carbon black masterbatch is ≤N1, and the visibility of the color stripes is ≤K1.
[0109] It can be seen from Examples 8 to 11 that, compared with using copolymerized polypropylene as the base resin, the polypropylene composite prepared by using homopolymerized polypropylene has fewer color stripes and lower color stripe visibility.
[0110] It can be seen from Example 8, Example 12 and Example 13 that the smaller the particle size of carbon black or the smaller the oil absorption value of carbon black, the prepared polypropylene composite has fewer color stripes and lower color stripe visibility.
[0111] It can be seen from Examples 8, 14 and 15 that both molecular sieves and mesoporous carbon can be used as mesoporous materials for the carbon black masterbatch of the present invention, and when the pore size of the molecular sieve is about 10 nm, the prepared polypropylene composite has fewer color stripes and lower color stripe visibility.
[0112] It can be seen from Example 1 and Comparative Example 1 that when the components are added in the form of masterbatch to prepare the polypropylene compound, the prepared polypropylene compound has a more excellent effect.
[0113] It can be seen from Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 that when the carbon black masterbatch lacks maleic anhydride grafted polypropylene, polar talc or mesoporous material, it is difficult to achieve the technical effect of the present invention. Figure 1 As shown, the color stripes are indicated by arrows in the figure. It can be seen that obvious color stripes appear on the surface of the prepared polypropylene composite, which can be seen visually.
[0114] It can be seen from Example 1, Comparative Example 5 and Comparative Example 6 that when the particle size or oil absorption value of carbon black is not within a specific range, it is difficult to achieve the technical effect of the present invention.
[0115] The foregoing examples are merely illustrative and are used to explain some features of the method of the present invention. The appended claims are intended to require the widest possible range that can be imagined, and the embodiments presented herein are demonstrated by the applicant's actual test results. Therefore, the applicant's intention is that the appended claims are not limited by the selection of examples that illustrate the features of the present invention. Some numerical ranges used in the claims also include sub-ranges therein, and changes in these ranges should also be interpreted as being covered by the appended claims where possible.
Claims
1. A carbon black masterbatch, characterized in that: The composition comprises the following components by weight: 10 to 20 parts of carbon black, 10 to 20 parts of mesoporous material, 10 to 20 parts of polar talc powder, 40 to 70 parts of maleic anhydride grafted material, and 0.2 to 1 part of auxiliary antioxidant; The D50 particle size of the carbon black is ≤20nm, and the oil absorption value of the carbon black is ≤100cm 3 / 100g.
2. The carbon black masterbatch according to claim 1, characterized in that: The pore size of the mesoporous material is 2 to 13 nm; and / or The mesoporous material is selected from one or more of zeolite, diatomaceous earth, molecular sieve and mesoporous carbon.
3. The carbon black masterbatch according to claim 1, characterized in that: The polar talc is organic carboxylic acid coated modified talc; and / or The D50 particle size of the polar talc is ≤18 μm.
4. The carbon black masterbatch according to claim 3, characterized in that: In the organic carboxylic acid coated modified talc, the content of organic carboxylic acid accounts for 0.4-1.2 wt %.
5. The carbon black masterbatch according to claim 1, characterized in that: The maleic anhydride grafted product is selected from one or more of maleic anhydride grafted polypropylene and maleic anhydride grafted POE; and / or The melt flow rate of the maleic anhydride grafted product at 230° C. and 2.16 kg is 3 to 120 g / 10 min; and / or The grafting rate of the maleic anhydride grafted product is 0.5 to 1.5%.
6. The method for preparing the carbon black masterbatch according to any one of claims 1 to 5, characterized in that: The carbon black and the mesoporous material are mixed, and then polar talcum powder, maleic anhydride grafted material and auxiliary antioxidant are added, mixed evenly, and granulated to obtain carbon black masterbatch.
7. Use of the carbon black masterbatch according to any one of claims 1 to 5 in the preparation of polypropylene compounds or in the automotive field.
8. A polypropylene composite, characterized in that The invention comprises the following components in parts by weight: 28 to 100 parts of polypropylene resin, 0.1 to 2 parts of the carbon black masterbatch according to any one of claims 1 to 5, 0 to 1 part of antioxidant, 0 to 0.5 part of light stabilizer, 0 to 0.5 part of lubricant, 0 to 10 parts of polyethylene resin, 0 to 30 parts of elastomer and 0 to 30 parts of mineral powder.
9. The method for preparing the polypropylene compound according to claim 8, characterized in that: The polypropylene compound is obtained by mixing polypropylene resin, carbon black masterbatch and other substances contained in the polypropylene compound, melt-extruding and granulating.
10. Use of the polypropylene compound according to claim 9 in the automotive field.
Citation Information
Patent Citations
Universal color master batch with high carbon black content and high melt flow rate and preparation method thereof
CN112552571A
Modified carbon black master batch as well as preparation method and application thereof
CN115260708A
Fiber-grade black master batch, preparation method thereof and application of fiber-grade black master batch in preparation of polyester fibers
CN118580643A
Compatibilized carbon black and a process and a method for using
US5571847A
Weather-resistant polypropylene composition and preparation method therefor and application thereof
WO2023138230A1